Disclosure of Communication in the Facebook and Impact Social Media on Worship Activities in Dakwah Faculty Students and Science of Communication Media of North Sumatera State University (UINSU) - Marlina Marlina; Moh. Hatta; Suwardi Lubis (Budapest International Research and Critics University, 2020)
This study aims to reveal the extent of openness of communication carried out among students of the Da'wah Faculty and UINSU communication and its impact on worship activities carried out by these students. Observations and interviews are techniques used to collect data in this study. Triangulation analysis method is also used to analyze the data obtained from respondents, descriptive analysis research method applied in this study. From 30 respondents taken with a percentage of 20 female respondents and 10 male respondents it was found that social media activities through Facebook had a special attraction and increased their confidence in communication. The impact felt by the respondents was more to the shift in the discipline of worship that they did when cool communicating with their virtual friends, recitations of the Koran that are usually done before prayer time arrives multiplied by the fun they are chatting, status updates or just looking at their Facebook wall.